(untitled) (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2026)
This article examines the discourse strategies used to express affection in English and Uzbek, with a particular focus on gender-based differences in communication. While previous studies have primarily explored lexical and pragmatic aspects of affectionate language, this research shifts the focus to discourse-level analysis, emphasizing how affection is constructed and conveyed in real communicative contexts. The study is grounded in the theoretical framework of Sociolinguistics and draws on the ideas of Deborah Tannen regarding gendered communication styles. A qualitative comparative method is employed, analyzing dialogue samples from everyday interactions in both languages. The findings indicate that English speakers tend to express affection more directly and verbally, whereas Uzbek speakers often rely on indirect strategies, such as care-based expressions and context-dependent cues. Gender differences are also evident: female speakers in both linguistic cultures demonstrate higher emotional expressiveness, while male speakers tend to use more restrained or implicit forms of affection, often embedding them in humor or supportive actions.